A DEMATEL-TODIM based decision framework for PV power generation project in expressway service area under an intuitionistic fuzzy environment. (20th February 2020) - Wu, Yunna; Wu, Chenghao; Zhou, Jianli; Zhang, Buyuan; Xu, Chuanbo; Yan, Yudong; Liu, Fangtong
Abstract: The expressway service area photovoltaic (ESAPV) projects have been greatly promoted due to the increasing passenger volume and the current development of electric vehicle industry. Site selection based on sustainability perspective is critical to the future construction of ESAPV. This paper puts forward a decision-making framework to ensure the validity of the ESAPV site selection. First, the index system meeting the characteristics of the ESAPV project is established. Second, in order to take into account the influence of subjective preference and objective justice on the results, this study chooses the Decision Making Trial and Evaluation Laboratory (DEMATEL) method to determine the weights of first-level indicators that lack objective data support and employs an integrated weighting method to determine the weights of second-level indicators. Third, the TODIM (an acronym in Portuguese of interactive and multi-criteria decision making) method which considers decision makers' risk aversion psychology is extended to triangular intuitionistic fuzzy environment combined with group decision-making theory. Finally, a case study in Hebei of China is carried out to verify the practicability of the systematic framework. The results indicate that the optimal project is located in Shijiazhuang. Highlights: This study establishes a four-stage decision framework for ESAPV site selection. The criteria system for ESAPV site selection is innovatively established. Triangular intuitionistic fuzzy numbers are utilized to describe the uncertainties. DEMATEL and maximum cross-entropy are used to determine the weights of criteria. The improved TODIM method is introduced to rank the optimal alternatives.